Study of water quality in ex-mining pits for fish cultivation in Gunung Mas regency, Central Kalimantan - Inel, Lukas; Minggawati, Infa; Serezova Augusta, Tania; Agustinus, Frid; Wirada, Fenky (Indonesian Society of Scientific Aquaculture (ISSA), 2024)
Ex-mining pit is a wide expanse, often becomes a problem, especially for the environment. Lack of information about the use of mining pits for fishing activities, especially for the studies on the quality of mining pits to support the growth of cultivated fish. This research was conducted in the village of Tanjung Riu, Gunung Mas Regency, Central Kalimantan Province, using two ex-mining ponds belonging to the community. The results show that the water quality for both mine pits with water parameters for: dissolved oxygen (DO) on average 6.09 mg/l – 7.45 mg/l, pH 2.94 – 3.54, Biological Oxygen Demand (BOD) 4.78 mg/L, temperature 30 -32 oC, turbidity 51.7-53.5 NTU, value of Total Dissolved Solids (TDS) 0.003 – 0.017 gr/L, mercury (Hg) content of 0.000247 mg/l - 0.000359 mg/l, the depth of the pool is 1.7 m – 2.74 m. The abundance of plankton is between 869 - 1106 cells/L, and abundance of benthos is between 264 - 352 ind/m2. The range of pond water quality based on second-class national water quality standards, which is suitable for fish cultivation with moderate abundance of plankton.